New approach of Double Weight Code Family Detection using reduced set of Fiber Bragg Gratings - Mohammed, A; Babekir, E.I; Elfadel, N.; Saad, N. M.; Anuar, Mat Safar; Syed Alwee Aljunid, Syed Junid; Mohamad Khazani, Abdullah (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org